FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN NYERI POST OPERASI SECTIO CAESAREA DI RS. RAFLESSIA BENGKULU - Metasari, Des; Sianipar, Berlian Kando (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
The action of Sectio cassarea (SC) is one of the alternatives for a woman in choosing the delivery process in addition to medical indications and non-medical indications, SC action will discontinue continuity or tissue linkage because of the incision that will release pain receptors. Early mobilization is a factor that can reduce post-surgical pain while relaxation technique is a non-pharmacological pain transfer method that can reduce the pain sensory component. The purpose of this research is to know the factors that can influence the decrease in intensity of postoperative SC pain which is the technique of mobilization and relaxation technique, this research is done in RS Raflessia Bengkulu in August until September 2017 with sample 40 peoples postpartum mother with accidental sampling technique sampling. This method of research using quasy experiment, with approach of One Group Pre-Post Test which aims to see the effect of early mobilization to the intensity of pain in patients post-sectio cessarea. The results of the study showed an average decrease in pain level after early mobilization of 2.2, a decrease of pain level after relaxation technique of 2.1 and there was an effect of early mobilization on the decrease of pain intensity with p value (0.000). It is suggested to the hospital to maximize the implementation of early mobilization of 6 hours postoperative on postpartum mother with SC and perform early mobilization technique to postpartum motherwith SC in a correct and correct way to reduce the pain due to surgical incision wound